2018
DOI: 10.2337/db17-0958
|View full text |Cite
|
Sign up to set email alerts
|

Podocyte-Specific Loss of Krüppel-Like Factor 6 Increases Mitochondrial Injury in Diabetic Kidney Disease

Abstract: Mitochondrial injury is uniformly observed in several murine models as well as in individuals with diabetic kidney disease (DKD). Although emerging evidence has highlighted the role of key transcriptional regulators in mitochondrial biogenesis, little is known about the regulation of mitochondrial cytochrome c oxidase assembly in the podocyte under diabetic conditions. We recently reported a critical role of the zinc finger Krüppel-like factor 6 (KLF6) in maintaining mitochondrial function and preventing apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…In view of the important role of podocytes on DKD [31], we next examined the effect of MYDGF deficiency on podocytes.…”
Section: Mydgf Deficiency Promotes Podocyte Injury In Dkd Micementioning
confidence: 99%
“…In view of the important role of podocytes on DKD [31], we next examined the effect of MYDGF deficiency on podocytes.…”
Section: Mydgf Deficiency Promotes Podocyte Injury In Dkd Micementioning
confidence: 99%
“…Interactions between these two types of cells occur in areas rich in extracellular matrix (ECM) ( 241 245 ). There are several factors affecting the mutual effect between ECs and PCs in pathological state, including changes in advanced glycation end products, increased leukocyte adhesion and inflammatory cytokines ( 246 , 247 ).…”
Section: Research Hotspots Of the Endothelial Dysfunction Of Diabetic...mentioning
confidence: 99%
“…It was demonstrated that KLF6 modulated the mitochondrial functions by preventing the activation of the cytochrome C-mediated intrinsic apoptotic pathway [ 75 ]. A subsequent study revealed that KLF6 was also involved in protecting the mitochondria from injury and apoptosis under diabetic conditions [ 76 ]. In the central nervous system (CNS), KLF6 interacted with STAT3 to coregulate the expression of genes involved in axon and corticospinal tract neurons regeneration following injury [ 77 ].…”
Section: Klf6 Roles In Normal Physiological Processesmentioning
confidence: 99%